The Influence of Learning Media on Students' Understanding of Simple Aircraft Material - Rusli Dedi Mustofa; Popy Aprilia; Wahyu Kurniawati (Publikasi Inspirasi Indonesia, 2023)
This article explains the use of media in learning as an intermediary to make it easier to convey learning material. Learning media is a very important factor in learning because learning media is related to students' learning experiences. Learning media is designed as well as possible by educators so that students can more easily absorb learning material and also increase students' stimulus for learning. On the other hand, researchers use literature study research methods to solve the problem topics discussed. Meanwhile, what is called the literature study research method is a research method carried out by researchers to complete research tasks by collecting data from books, journals and other sources of data from literature. That's why it is called literature study research. The results of the research show that learning media has a big influence on students in understanding Simple Plane material in science subjects in elementary schools. Therefore, teaching staff are required to be able to develop creative learning media and of course be able to attract students' interest in learning seriously.